Stock market integration and causality between Malaysia, United States, Singapore, China And Indonesia: during and after financial crisis / Muhammad Auquasyah Azmin - Azmin, Muhammad Auquasyah (Faculty of Business and Management, 2019)
A number of previous studies (theoretically and empirically) have examined cointegration and causal linkages among the global markets, This study comes across when the global economic event (i.e. financial crisis) gives an impact towards Malaysia stock market integration. 'The sub—prime financial crisis initially affected the Malaysia economy, hcnvever. the recovery in the Malaysia and other Asian countries took place at a much faster pace than during the previous crisis. Thus, due to this context, the purpose Of this study is to examines the stock market integration and causal relationship between Malaysia, United States, Singapore, China and Indonesia, focusing on the periods Of during and post financial crisis. The selected countries being choose according to the top most emerging stock markets related to Malaysia. Five variables used for this study involving Kuala Lumpur Composite Index (KLCI), Standard & Poor's 500 (SNP500), Straits Times Index (STI), Jakarta Composi te Index (JCI) and Shanghai Stock Exchange (SSEI), The entire samples collected from the DataStream from 2007 until 2017. The result of this study that there is a cointegraaon relationship between KLCI and SNPSOO, STL JCL and SSEI imply causality during and post crisis.